Remarques sur les premiers troubadours - Pietro G. Beltrami (Lecturae Tropatorum, 2018)
This paper points out the faults in the view that troubadour poetry developed expressing a new culture in medieval courts (fin’amor, ‘amour courtois’), as well as in the view that it developed expressing broadly religious issues (this of course does not mean that religious education and culture in many a troubadour is called into doubt). The new feature in comparison with ‘traditional’ sung poetry was the fact that performing songs and listening to them had become a social habit in aristocratic courts, so that singing could─in some instances─take on a public as well as a political meaning. Thus, the preservation and trasmission of poetic texts, and the interest in their authors as particular individuals, became important as never before, but this dates only from the time of Guilhem IX. The paper surveys some features in the poetry of early troubadours (Guilhem, Jaufre Rudel, Cercamon, Marcabru) and argues that before Bernart de Ventadorn there are only isolated statements of the so-called fin’amor poetics, which can be considered as fully developed only in Bernart’s works.